2021
DOI: 10.3389/fgene.2021.627050
|View full text |Cite
|
Sign up to set email alerts
|

Adapting CRISPR/Cas9 System for Targeting Mitochondrial Genome

Abstract: Gene editing of the mitochondrial genome using the CRISPR-Cas9 system is highly challenging mainly due to sub-efficient delivery of guide RNA and Cas9 enzyme complexes into the mitochondria. In this study, we were able to perform gene editing in the mitochondrial DNA by appending an NADH-ubiquinone oxidoreductase chain 4 (ND4) targeting guide RNA to an RNA transport-derived stem loop element (RP-loop) and expressing the Cas9 enzyme with a preceding mitochondrial localization sequence. We observe mitochondrial … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(44 citation statements)
references
References 44 publications
1
36
0
Order By: Relevance
“…Studies using ZFN ( Minczuk et al, 2008 ; Gammage et al, 2014 , 2016 , 2018 ) and TALENS ( Bacman et al, 2013 ; Reddy et al, 2015 ; Yang et al, 2018 ) have also been used to successfully target pathogenic variants in the mitochondrial genome to eliminate these mutant genes and restore wild-type phenotype. Although a lot of these techniques have been readily adapted to editing the nuclear genome, slight modifications have to be made to target them to mitochondria to modify mtDNA ( Hussain et al, 2021 ). For instance, while CRISPR/Cas9 has been adopted for base editing in the nuclear genome, it has been challenging to do the same with the mitochondrial genome because of the difficulty associated with the delivery of guide RNA into the mitochondria ( Greenfield et al, 2017 ; Hussain et al, 2021 ; Yang et al, 2021 ).…”
Section: Therapeutic Strategies and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies using ZFN ( Minczuk et al, 2008 ; Gammage et al, 2014 , 2016 , 2018 ) and TALENS ( Bacman et al, 2013 ; Reddy et al, 2015 ; Yang et al, 2018 ) have also been used to successfully target pathogenic variants in the mitochondrial genome to eliminate these mutant genes and restore wild-type phenotype. Although a lot of these techniques have been readily adapted to editing the nuclear genome, slight modifications have to be made to target them to mitochondria to modify mtDNA ( Hussain et al, 2021 ). For instance, while CRISPR/Cas9 has been adopted for base editing in the nuclear genome, it has been challenging to do the same with the mitochondrial genome because of the difficulty associated with the delivery of guide RNA into the mitochondria ( Greenfield et al, 2017 ; Hussain et al, 2021 ; Yang et al, 2021 ).…”
Section: Therapeutic Strategies and Future Directionsmentioning
confidence: 99%
“…Although a lot of these techniques have been readily adapted to editing the nuclear genome, slight modifications have to be made to target them to mitochondria to modify mtDNA ( Hussain et al, 2021 ). For instance, while CRISPR/Cas9 has been adopted for base editing in the nuclear genome, it has been challenging to do the same with the mitochondrial genome because of the difficulty associated with the delivery of guide RNA into the mitochondria ( Greenfield et al, 2017 ; Hussain et al, 2021 ; Yang et al, 2021 ). However, a CRISPR-free technology involving the use of bacterial cytidine deaminase toxin has been recently developed for use in mitochondrial base editing ( Mok et al, 2020 ).…”
Section: Therapeutic Strategies and Future Directionsmentioning
confidence: 99%
“…As such, CRISPR-Cas9 technology has quickly been coupled with iPSCs to study disease-causing genetic variation in humans. Until recently, targeting of the mtDNA with CRISPR-Cas9 was unfeasible due to challenges in targeting the guide RNA and Cas9 protein to the mitochondrial matrix [74][75][76]. Consequently, most studies to-date have utilized CRISPR-Cas9 technologies to edit nDNA-encoded mitochondrial genes.…”
Section: Targeted Gene-editing and Its Use In Identifying Functionally Relevant Variantsmentioning
confidence: 99%
“…While mtDNA gene editing using CRISPR/Cas9 remains more difficult than nuclear editing, recent studies have demonstrated success doing so. In updating the method for targeting the highly inaccessible mitochondrial matrix where the mtDNA is housed, scientists have shown that by combining (1) an endogenously expressed Cas9 with a mitochondrial targeting sequence with (2) an NADH:ubiquinone oxidoreductase chain 4 targeting guide RNA, in conjunction with an RNA transport-derived stem loop element, the mtDNA can be edited [76]. In addition to advances in CRISPR/Cas9, a non-CRISPR-based approach utilizing bacterial cytidine deaminase toxin demonstrated efficiency in catalyzing C•G-to-T•A conversions within the mtDNA with high target specificity.…”
Section: Targeted Gene-editing and Its Use In Identifying Functionally Relevant Variantsmentioning
confidence: 99%
“…CRISPR-Cas9 targeting of mtDNA has been challenging due to a lack of recognition sites for the Cas9 enzyme, and the poor delivery of sgRNA into mitochondria. However, recent studies have described the generation of gene-editing systems that can be used for targeting mitochondrially-encoded mitochondrial genes (MEMGs) (Mok et al, 2020;Hussain et al, 2021). It is clear from both ethidium bromide and enzymatic depletion of mtDNA in cancer cells, that MEMGs are also required for the proliferation of many cancer cell lines (Herst et al, 2004;Kukat et al, 2008).…”
Section: Essential Mitochondrial Genesmentioning
confidence: 99%